Quality Evaluation of Ground Water Near Point Source in Urban Area for Assessment of Its Potential for Application - Machiraju1, P.V.S.; V.V. Satyavani2, Ch.; Krishna Murty3, M. (Asian Journal of Chemistry, 2014)
In the present scenario of urbanization especially in metro, urban and semi urban areas, the accumulation of domestic wastes are enormously enhancing and management of the municipal solid wastes have become very difficult. The domestic wastes are being deposited even in and around residential localities by municipal or metro authorities. The municipal dump yards act as a point source of pollution. Due to percolation or leaching of the solid substances from these wastes enter the ground water around the dump yard and change the chemical characteristics and deplete the quality of ground water in the nearby areas. The presence of microbial content can also contaminate the ground water and can cause health hazards. Keeping in view the present situation of rapid urbanization, the present research programme is mainly focused on characterization of ground waters near a point source (municipal dump site) in Kakinada city of Andhra Pradesh for physico-chemical parameters, viz., pH, electrical conductivity, total dissolved solids, total hardness, Ca2+, Mg2+, total alkalinity, CO32–, HCO3–, OH–, Na+, K+, F–, Cl–, SO42–, NO3–, PO43– and determination of irrigation parameters like percent sodium, sodium adsorption ratio, residual sodium carbonate, Kelly's ratio, magnesium hazard to evaluate the quality of ground water for considering their suitability for drinking, domestic and irrigation. The ground waters are also characterized for bacterial spps to assess the bacterial contamination of the waters in the study area. The results revealed that the waters are chemically contaminated and also present with magnesium hazard indicating their unsuitability for drinking, domestic and irrigation. The presence of bacteria viz., E. coli, Klebsiella, Pseudomonas, Proteus and Enterobacter indicate the bacterial contamination of waters and their unsuitability for human consumption.